Atributos microbiológicos de um solo construído vegetado com gramíneas após mineração de carvão em Candiota/RS. - Holanda Neto, Manoel Ribeiro (2011)
The city of Candiota/RS has the largest coal mine in Brazil, with 38% of the entire national product extracted from open-pit mines. The inadequate disposal process of tailings from mining leads to loss of soil, surface water and changes in physical, chemical and biological attributes. The restoration degraded areas involves a set of actions that provide the functionality to restore ecosystem. The Revegetation is an important step in recovery of these soils which aims the landscaping the area, erosion control and restoration of physical, chemical and biological soil properties. This work aimed to evaluate the effect of different cropping systems on chemical and microbiological attributes of a constructed soil after the coal extraction. In an area of coal mining of the, located in Candiota, RS. The experimental design was composed by randomized blocks with four replications, with the following treatments of crops: T1 - Capim Vaqueiro (Cynodon dactilon (L.) Pers.); T2 - Braquiária (Brachiaria brizantha (Hochst.) Stapf); T3 - Capim Tanzânia (Panicum maximum Jacq); T4 - Braquiária humidícula (Brachiaria humidicola (Rendle) Schweickt); T5 - Hemártria (Hemarthria altissima (Poir.) Stapf & C. E. Hubbard); T6 - Grama Tifton (Cynodon dactilon (L.) Pers.); T7 - Capim Vaqueiro+Grama Tifton; T8 - Capim Vaqueiro+Hemártria; T9 - Braquiária brizantha+Grama Tifton; T10 - Braquiária brizantha+Hemártria; T11 - Capim Tanzânia+Grama Tifton; T12 - Capim Tanzânia+Hemártria; T13 - Braquiária humidícula+Grama Tifton; T14 - Braquiária humidícula+Hemártria, and T15 (SC) constructed soil without vegetation. Soil samples (0-0,05m) were collected in september of 2009 to determine chemical and microbiological attributes. The results were compared between treatments using analysis of variance and Tukey Test at 5% significance and a comparison of each treatment with control (T15) was made using the Dunnett Test at 5% of probability. It was observed that the addition of fertilizer and lime for the cultivation of crops increased the pH values, electrical conductivity, calcium, magnesium, potassium, phosphorous, manganese, zinc, copper, and exchangeable sodium, the organic carbon and soil basal respiration for crop cultivation, when compared to non-vegetated constructed soil These results suggest that all cultures tested may be promising in the recovery area over time. The treatments Hemártria and Braquiária humidícula+Hemártria showed the higher contents of microbial biomass carbon in constructed soil. The crops studied, in general, promoted an increased in mycorrhizal colonization and sporulation and also AMFs species when compared with non-vegetated constructed soil, reducing the impact caused by interference of mining.